2020
DOI: 10.3126/jist.v25i1.29450
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Springwater In-Situ Parameters in the Bhusundi Catchment, Gorkha, Nepal

Abstract: Spring is a concentrate flow of groundwater that appears at the earth’s surface. The seasonal variations of spring water quantity and quality are required to ensure water availability during the dry season. The research focuses on the seasonal variations of spring water quantity and quality with the spatial distribution of springs interlinking with geological settings of the area. Research framework has been established comprising spring inventories before and after the monsoon in 2017 AD of the Bhusundi catch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Studies on springs largely include spring hydrology and water quality assessments. Spring hydrology has been studied by Valdiya & Bartarya (1989), Negi & Joshi (2002), Adhikari et al (2021), Dhungel et al (2016), Rawat et al (2016), Poudel & Duex, (2017), Ghimire et al (2019), Tambe et al (2012), Pokhrel & Rijal (2020), Verger et al (2008) and Kumar & Sen (2018b) among others. Spring water quality assessments have been done by Kumar et al (1997), andKothyari (2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on springs largely include spring hydrology and water quality assessments. Spring hydrology has been studied by Valdiya & Bartarya (1989), Negi & Joshi (2002), Adhikari et al (2021), Dhungel et al (2016), Rawat et al (2016), Poudel & Duex, (2017), Ghimire et al (2019), Tambe et al (2012), Pokhrel & Rijal (2020), Verger et al (2008) and Kumar & Sen (2018b) among others. Spring water quality assessments have been done by Kumar et al (1997), andKothyari (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Spring water quality assessments have been done by Kumar et al (1997), andKothyari (2003). Thapa et al (2020), Pokhrel & Rijal (2020) and Rani et al (2021) and others. Studies on spring water runoff over the Himalayan region are hardly found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation